Programmed calculation of individual limits of operational range of flight restrictions AN-24, AN-26 - Білогузов B. C.; Мещишен, Д. К. (Proceedings of National Aviation University (archive), 2020)
The structural scheme and basic principles of functioning of the computer program General Performance, which is a key point in the method of operational control aerodynamic state of the aircraft